2018
DOI: 10.3791/57759
|View full text |Cite
|
Sign up to set email alerts
|

Methods for the Study of Regeneration in <em>Stentor</em>

Abstract: Cells need to be able to regenerate their parts to recover from external perturbations. The unicellular ciliate Stentor coeruleus is an excellent model organism to study wound healing and subsequent cell regeneration. The Stentor genome became available recently, along with modern molecular biology methods, such as RNAi. These tools make it possible to study single-cell regeneration at the molecular level. The first section of the protocol covers establishing Stentor cell cultures from single cells or cell fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…While diverse chemical treatments lead to a similar oral regeneration response [26], the sucrose shock was found to be the most reproducible-producing the cleanest MB removal, leaving sharp borders at the detachment zone. Here, we follow previously published protocols [11,27] with only slight modifications. Briefly, Stentor were exposed to a 10% sucrose solution for 2-3 min, which elicited synchronous MB shedding in more than 80% of the cases (electronic supplementary material).…”
Section: (C) Regenerative Prowess Of Stentormentioning
confidence: 99%
“…While diverse chemical treatments lead to a similar oral regeneration response [26], the sucrose shock was found to be the most reproducible-producing the cleanest MB removal, leaving sharp borders at the detachment zone. Here, we follow previously published protocols [11,27] with only slight modifications. Briefly, Stentor were exposed to a 10% sucrose solution for 2-3 min, which elicited synchronous MB shedding in more than 80% of the cases (electronic supplementary material).…”
Section: (C) Regenerative Prowess Of Stentormentioning
confidence: 99%
“…DNA-dependent RNA synthesis is required to supply the new protein required during intermediate stages of 21 regeneration, but not during the later stages. Depending on temperature, medium, and other unknown factors 22 [19], the total regeneration time ranges between 8-10 hours at 20-25 °C.…”
Section: Regenerative Prowess Of Stentormentioning
confidence: 99%
“…of the above staging. Oral regeneration in S. coeruleus was induced by sucrose shock, with slight modifications 34 from published protocols [21,5], which were based on historical works (see supp. materials).…”
Section: Regenerative Prowess Of Stentormentioning
confidence: 99%
“…Cultures were maintained in dishes containing 50mL of sterile filtered water from the pond where the cells were isolated. Cells were fed twice a week with Chlamydomonas reinhardtii (strain cc125, kind gift from the Marshall lab) as has been done previously for Stentor coeruleus [10,22] and kept at 22ºC in ambient room light with indirect sunlight from windows in lab. In this way the cells were under loosely controlled light/dark cycles, as it was previously reported that cells divide at night [13].…”
Section: Cell Isolation and Culturementioning
confidence: 99%
“…To maintain these organisms long-term in the lab, I established stable cultures of isolated S. polymorphus using the same laboratory culturing methods already used for S. coeruleus [22]. Briefly, S. polymorphus cells were washed in sterile filtered pond water (hereafter referred to as pond water) and ~300 cells were placed in a small glass jar containing 50 mL of pond water.…”
Section: Isolation Identification and Culture Of Stentor Polymorphusmentioning
confidence: 99%